An investigation into school finance committees in administering financial resource : a case study of the Phokoane Circuit, Limpopo Province - Phakwago, Hubale Ruth (My University, 2022)
Schools depend on the funds allocated by the government, parents and to an extent donation from Non-Governmental Organisations (NGO). According to the Public Finance Management Act, 1999 (Act 1 of 1999), all public institutions must utilise funds in an effective, efficient and transparent manner. Schools as one of the public institutions are therefore expected to meet the expectations. To ensure compliance and smooth administration of public finances in schools, the government developed rules, legislations and policies as guiding tools in the administration of finances. In the school setup it is the responsibility of the school governing bodies guided by the principals to ensure proper and lawful usage of funds (South African Schools Act, 1996, Act 84 of 1996). Furthermore, South African Schools Act, 1996(Act 84 of 1996), stipulates that the responsibilities and the accountability of the finances rest on the shoulders of the Finance Committee. It is therefore necessary for the Finance Committees to have the necessary competencies in financial management and administration. The study aimed at investigating the competency of the Finance Committees in administering the financial resources in Phokoane Circuit schools. The study was guided by the Professionalism Theory to address the research problem. Professionalism theory also assisted in the methodology used to collect and analyse data to obtain trustworthy findings. The study is a qualitative research enquiry in nature. The study employed qualitative research methods in which data was collected through interviews and document study. Four no- fee schools were sampled. The treasurer, finance officer, SGB Chairperson and Deputy Chairperson of each sampled school constituted the participants of the study. The study revealed lack of knowledge and skills in financial administration, non compliance of the legislation frameworks and the financial policies, insufficient accountability; control and monitoring of finances, lack of teamwork, incompetence of Finance Committees members, insufficient financial resources and overlapping of responsibilities between the principals and Finance Committees in schools. Based on these findings the study recommends that in-depth training of Finance Committee be undertaken, Finance Committee members are developed in financial legislative frameworks and policies. Furthermore, the study recommends that the Finance Committee be developed on programmes in accounting, monitoring and control of finances. Additionally, the study also recommends that teamwork on the financial activities be enhanced and that financial resources in schools be adequately available. Through the development of members of Finance Committee the overlapping responsibilities between the principals and the committee will be avoided.
Thesis(MPA.) -- University of Limpopo, 2022
Keywords: Finance administration; Finance policy; Finance committee; Budget; Control and monitoring; Reporting; Procurement; Competency; Public finance administration; Education -- Finance; School facilities -- Finance